Improving End-Point Position Control in Hydraulic Testing Machines with a Fuzzy Logic Based Approach - Serkan Anlak; Ekrem Düven (Journal of Advanced Research in Natural and Applied Sciences)
During the repetitive operation of hydraulic testing machines, some undesirable vibration movements and non-compliance with the set value may occur at the piston end-point, which is the output of the system. PID (Proportional-Integral-Derivative) control is widely used in such systems in practical applications. However, the use of a standard (fixed coefficient) PID control alone cannot completely eliminate problems such as endpoint vibration and/or non-compliance of the endpoint position with the set value, caused by dynamic parameter changes in the hydraulic system. In the current state of the applications, when such a situation is encountered, the controller coefficients need to be readjusted by a human operator. In this study, to avoid this need and automatically adjust PID controller coefficients, a fuzzy logic-based computation approach has been developed and applied to the existing control system. A hydraulic system was designed and realized to test the developed method. The end-point position control of the system was established and improved utilizing the developed approach. With this development, an improvement of more than 10% was achieved in the adjustment of the hydraulic testing machine end-point oscillation amplitude to the set value. The use of this method also eliminates the need for human operators to readjust the controller parameters in case of long-term operation of hydraulic test systems.